Dietary intake alters behavioral recovery and gene expression profiles in the brain of juvenile rats that have experienced a concussion - Mychasiuk, Richelle; Hehar, Harleen; Ma, Irene; Esser, Michael J. (Frontiers in Behavioral Neuroscience, 2015)
Concussion and mild traumatic brain injury (mTBI) research has made minimal progress diagnosing who will suffer from lingering symptomology or generating effective treatment strategies. Research demonstrates that dietary intake affects many biological systems including brain and neurological health. This study determined if exposure to a high fat diet (HFD) or caloric restriction (CR) altered post-concussion susceptibility or resiliency using a rodent model of pediatric concussion. Rats were maintained on HFD, CR, or standard diet (STD) throughout life (including the prenatal period and weaning). At postnatal day 30, male and female rats experienced a concussion or a sham injury which was followed by 17 days of testing. Prefrontal cortex and hippocampus tissue was collected for molecular profiling. Gene expression changes in BDNF, CREB, DNMT1, FGF-2, IGF1, LEP, PGC-1α, SIRT1, Tau, and TERT were analyzed with respect to injury and diet. Analysis of telomere length (TL) using peripheral skin cells and brain tissue found that TL in skin significantly correlated with TL in brain tissue and TL was affected by dietary intake and injury status. With respect to mTBI outcomes, diet was correlated with recovery as animals on the HFD often displayed poorer performance than animals on the CR diet. Molecular analysis demonstrated that diet induced epigenetic changes that can be associated with differences in individual predisposition and resiliency to post-concussion syndrome.